Implementasi Kegel Exercise terhadap Nyeri Menstruasi pada Siswi Kelas X di SMK - Indah Christiana; Rizki Fitrianingtyas; Elmi Nur Hidayati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2019)
Dsymenorrhea or abdominal pain is a gynecological complaint because of the imbalance of the hormone progesteon in the blood causing pain that comes from uterine cramps. The nature of the degree of pain varies, ranging from mild to severe, severe pain conditions can interfere with daily activities. One therapy to overcome the problem of menstrual pain is kegel exercise. Kegel exercise is a pelvic floor muscle exercises (ODP). The purpose of this study is to determine the implementation of kegel exercise against menstrual pain in grade X students in SMK Sanyanjung Banyuwangi Year 2017. The design in this study used pre experimental research design with one group pretest and postest design. Technique of collecting data using check list then analyzed by using Wilcoxon test with SPSS 23 for windows with α 0,05. Sampling technique using simple random sampling, With a sample of 30 respondents who aged 15-17 years in SMK Sritanjung Banyuwangi. Based on the results of the study of 30 respondents almost half of 46.7% (14 respondents) before giving kegel exercise experience moderate menstrual pain and almost half of 40% (12 respondents) after being given kegel exercise mild menstrual category pain. From the calculation of SPSS 23 for windows with Wilcoxon test obtained Asymp.Sig (2- tailed) value = 0,000 <α = 0.05 then Ho in reject Ha in receipt which means there is a significant influence on the kegel exercise against menstrual pain. The results of this study are expected to improve the knowledge of respondents in the management of dysmenorrhea by doing kegel exercise to reduce the level of menstrual pain.